A Nutritional and Anthropometric Analysis of the Double Burden of Malnutrition in Children Under Two in Madagascar - Rosita Rotella; María Morales-Suarez-Varela; Agustín Llopis-Gonzalez; Jose M. Soriano (Children)
Background: Almost half of all deaths worldwide in children under five are related to malnutrition. Malnutrition encompasses a wide array of nutritional conditions and emerging evidence indicates a growing overlap of these different forms of malnutrition. Nutrimetry, which combines assessments of height-for-age (HAZ) with BMI-for-age (BMIZ) to offer a more integrated assessment of nutritional status, can be particularly useful in low-resource settings to correctly reflect the complex interplay of stunting and overweight. Objective: The objective of this study is to explore the impact of malnutrition on children in Madagascar and demonstrate how integrating HAZ assessments with BMIZ can reveal the double burden of malnutrition—encompassing both undernutrition and overnutrition—within the same population. Methods: This cross-sectional observational study employing Nutrimetry was carried out in rural communities in the Itasy region of Madagascar. A systematic random sampling method was used to choose the 500 women to invite to participate from the approximately 5000 who formed the pool of potential participants. A total of 437 were able to be invited and all invited women agreed to participate, resulting in 437 mother–child (0–24 months) pairs being included in the study. Results: Chronic undernutrition or thinness (31.6%), overweight and obesity (21.3%), and stunting (57.6%) were prevalent among the children included in the study. Among children with chronic undernutrition, 55.06% were identified as stunted. Among children with overweight or obese, 61.03% were identified as stunted. This highlights a significant overlap between inadequate weight and stunting. A socioeconomic analysis revealed significant barriers, including limited financial resources and poor dietary diversity, exacerbating malnutrition. Maternal nutritional status and breastfeeding practices also emerged as critical determinants of child nutritional outcomes. Conclusions: The study underscores the importance of prioritizing height assessments as a preliminary step in nutritional evaluations to prevent undetected acute malnutrition.